Desenvolvimento de métodos para análise de tortas de oleaginosas por espectrometria de emissão óptica com plasma indutivamente acoplado e fluorescência de raios X por reflexão total - Luciene Vertello de Resende (2015)
This work describes the development and application of two analytical methods for determination of inorganic constituents in jatropha, sunflower, turnip, lupine, castor, rapeseed, palm and pequi oil-bearing crops aiming to evaluate their potential for use as organic fertilizer. The first method consists of acid digestion in the closed-vessel-microwave system applying HNO3 and H2O2. Measurements were performed using a ICP OES for determination of Ca, Cd, Cr, Co, Cu, Fe, K, Mg, Mn, Ni, Pb and Zn in the biodiesel press cake. The performance of the method was evaluated by analysis of CRM 1547 - CRM peach leaves and 1570a - Spinach leaves. Recoveries are in the acceptable range of 80-110%, for the levels of concentrations evaluated. Precision in terms of repeatability, were below 5% for most elements assessed. The LQ values obtained are suitable for analysis of organic fertilizer since they achieve the minimum levels of nutrients and maximum contaminant allowed in organic fertilizers in accordance to the Brazilian legislation. An extraction procedure using block digester with citric acid, neutral ammonium citrate and diethylenetriaminepentaacetic acid was applied for Ba, Ca, Cd, Cr, Co, Cu, Fe, Mg, Mn, Ni, Pb and Zn by ICP OES to estimate the available fraction of nutrients in biodiesel press cakes. The second part of this work consisted in the development and optimization of a method for determining P, S, Cl, K, Ca, Cr, Mn, Fe, Ni, Cu, Zn, Br, Rb, Sr and Pb by total reflection X-ray fluorescence - TXRF. The influence of the sample mass, Triton X-114 concentration and sonication time on the slurry preparation step were evaluated by the 23 factorial design with center point. The optimization of the method was conducted by evaluating the following parameters: PI (Ga, or Y) and signal acquisition time. The selectivity, trueness and precision were studied from spiked samples and certified reference materials (CRM 029-50, NIST 1573a, NIST 1547 and NIST 1567a). The recovery results are in the range 82-114%, for the majority of the investigated analytes and the relative standard deviations were less than 11.5%. The obtained LD are suitable for the purpose of the method. As regards selectivity, it is concluded that the method is not suitable for determination of Cd at concentrations 3 mg kg-1, since any possible peak of Cd L (3.126 keV) line is strongly suppressed by K K (3.313 keV) peak to the background level. The results of the elemental determination in press cakes obtained by TXRF were dissonant with those obtained by ICP OES for some elements assessed. The heterogeneity of the samples may have contributed to the observed differences. TXRF method is noteworthy since it displays an easy and simple sample preparation, a shorter time of analysis and consequently a high analytical frequency, minimal risks of contamination and losses by volatilization, generation of small amounts of waste, plus it features low cost for implementation. The developed and optimized analytical methods showed characteristics that qualify them for analysis of oilseed cakes, in accordance with Brazilian legislation.